Primary central nervous system ALK-positive anaplastic large cell lymphoma with CD56 abnormally expression in a Chinese child: Challenge in diagnostic practice - Liu, Qian (Int J Immunopathol Pharmacol, 2020)
Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALK + ALCL) is most frequent in youth and possesses a broad morphologic spectrum. However, involvement in central nervous system (CNS) is definitely rare. The case we presented was a 12-year-old Chinese male who presented with headache and emesis for a couple of days. The neoplastic component was smaller cells resembling starry-sky growth pattern and immunohistochemical stained positively for CD30, ALK1, and CD56. Monoclonal T-cell receptor (TCRγ) gene rearrangement and gene translocation involving ALK identified by fluorescence in situ hybridization (FISH) using ALK break apart probe supported the diagnosis of ALK + ALCL. This case showed ALK + ALCL occur in a rare site with an abnormal CD56 expression. Awareness of this entity is important to distinguish it from other intracranial lymphoma.